The relationship between different laying hen housing systems in Lithuania and egg production quality and chemical composition - Asta Racevičiūtė-Stupelienė; Vilma Vilienė; Saulius Bliznikas; Vilma Šašytė; Monika Nutautaitė (Cogent Food & Agriculture, 2023)
AbstractEgg consumers are becoming increasingly concerned about animal welfare, so it is crucial to develop a better understanding of whether alternative housing systems lead to higher quality eggs. So, the current study was designed to assess the egg quality characteristics, sensory features, fatty acid profile, and cholesterol levels of eggs produced in enriched caging and barn housing systems. An experiment was conducted on Lohmann Brown Classic line laying hens (aged 28–48 weeks) fed analogous feed and housed in enriched cages and barn housing systems. Eggs’ quality traits, nutritional value, and sensory acceptance were evaluated. Hens kept in enriched cages had higher liveability and lay rates but lower feed consumption and feed conversion ratio (FCR) at almost all trial periods. Barn-laid eggs were heavier and had larger yolks; enriched cage eggs showed higher albumen, Haugh unit (28, 32, 36 weeks of age), stronger and thicker eggshells (32 weeks of age); barn-laid eggs stronger and thicker eggshell (48 weeks of age), higher SFA (start of the trial) and PUFA (at the end) contents. The differences between enriched cage and alternative barn housing systems are negligible, as no clear trend was discovered between them during different trial periods while hens were fed an identical diet.